Extended School Time: Impact on Learning and Teaching - Mendes, Pedro Cabral (2021)
This paper presents and assesses the effects of an Extended School Time project (ESTp), with a working day of 8 contact hours, that aimed to develop the students as a whole in its academic, artistic, sport, social and human dimensions. Based in active and integrated pedagogical practices, the project promoted the integration of knowledges, curiosity, sense of criticism, creativity, sharing solidarity and the conviviality of students. This project was applied to a 6th grade class with 20 pupils (11.2±0.68 years old). Using a qualitative methodology, 13 semi structured interviews were applied to 3 types of participants: 6 pupils, 5 parents (42.6±4.54 years old) and 2 teachers (60±4 years old), in order to analyze their perceptions regarding the project. Results show that each group valued different aspects of the project. The pupils valued activities that emphasized challenge, communication, creativity, and autonomy, as well as activities of academic continuity. The parents focused mostly on the occupational component of Extended School Time (ESTp), and the teachers on its effects on social and self-development of the pupils. This development was reflected in an improved peer-to-peer relationship and in a greater sense of belonging to school. The convergence verified in this ESTp, between cognition and the artistic, social and sport education, sought to promote the main goal of the School, an instruction that promotes a global (including multicultural and universal) development of the pupils’ capabilities.